Exploring E-nose for sensing flavor profile of indigenous aromatic rice (Mushk Budiji) during storage - Ufaq Fayaz; Syed Zameer Hussain; Bazila Naseer; Fehim J. Wani; Nazrana Rafique Wani; Sobiya Manzoor (Sensing and Bio-Sensing Research, 2025)
Despite the popularity of Mushk Budiji rice, changes in the flavor profile of Mushk Budiji rice in storage remains unclear. Herein, the effect of packaging materials and storage conditions on the flavor profile of Mushk Budiji rice was investigated. Results showed that the average percentage of different volatile compounds increased when Mushk Budiji rice was stored in laminated bags under accelerated conditions. Results revealed that the E-nose aroma score significantly (p ≤ 0.05) increased from 2.17 to 3.09 under ambient storage conditions while as it increased from 2.17 to 3.38 under accelerated conditions. Additionally, under accelerated conditions the free fatty acid content, peroxide values and catalase activity significantly increased (p ≤ 0.05) from 2.90 % to 4.10 % and 0.44 to1.63 meq/kg & 3.74 to 4.00 U/mg respectively. This study will therefore pave a way forward to identify the flavor changes in Mushk Budiji rice under different storage conditions.